Aplikasi Proses Stokastik pada Penentuan Rumus Harga Opsi Menurut Black Scholes - AZIZ, Abdul ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There are lots of models used to determine the formula of pricing option. The most populer one is the Black Scholes pricing options model. His model is in the form of stochastic diferential equation which involves stochastic process in it. This thesis discuss how to define Ito Integral, apply its theory in the formation of Black Scholes pricing option model, and determine the formula of Black Scholes pricing option. The result of this study is the formula of Black Scholes pricing option.